Health of Fish Communities in the Lower Reaches of the Dongjiang River - MA Zhuoluo; HU Lianghe; JIANG Renfei; WANG Sai (Renmin Zhujiang)
Dongjiang River is an important water source and ecological corridor in the Guangdong-Hong Kong-Macao Greater Bay Area.Understanding the health of fish communities in the lower reaches of this river is vital for the water ecological protection of the basin.This paper investigates the fish in the lower reaches of the Dongjiang River,and the abundance index (dM) and Shannon Weiner index (H′) are selected to evaluate the community health,and the relationship between them and water quality factors is explored.The results show that there are 7 orders,19 families,43 genera,and 50 species of fish found in the lower reaches of this river,of which Cypriniformes is the largest and Perciformes is the second,with 10 species of exotic fish.There is a significant or extremely significant negative correlation between the health of fish communities and water pollution factors such as CODCr,BOD5,and TP,indicating that water pollution affects the health of fish communities.The river encroachment,rigid transformation,and the construction of gate and dam facilities disrupting habitats have also adversely influenced fish communities.Exotic fish have been found in most sampling sites and are more dominant in polluted rivers.It is necessary to develop scientific management strategies and measures from various aspects,including improving river water quality,restoring the diversity and connectivity of fish habitats,and strengthening the management and prevention of exotic fish. Finally,the protection and restoration of fish in the river can be advanced.